Executive summary of the KDIGO 2021 Clinical Practice Guideline for the Management of Blood Pressure in Chronic Kidney Disease - Cheung, Alfred K; Chang, Tara I; Cushman, William C; Furth, Susan L; Hou, Fan Fan; Ix, Joachim H; Knoll, Gregory A; Muntner, Paul; Pecoits-Filho, Roberto; Sarnak, Mark J; Tobe, Sheldon W; Tomson, Charles R V; et al. (Kidney international, 2021)
The Kidney Disease: Improving Global Outcomes (KDIGO) 2021 Clinical Practice Guideline for the Management of Blood Pressure in Chronic Kidney Disease for patients not receiving dialysis represents an update to the KDIGO 2012 guideline on this topic. Development of this guideline update followed a rigorous process of evidence review and appraisal. Guideline recommendations are based on systematic reviews of relevant studies and appraisal of the quality of the evidence. The strength of recommendations is based on the "Grading of Recommendations Assessment, Development and Evaluation" (GRADE) approach. The scope includes topics covered in the original guideline, such as optimal blood pressure targets, lifestyle interventions, antihypertensive medications, and specific management in kidney transplant recipients and children. Some aspects of general and cardiovascular health, such as lipid and smoking management, are excluded. This guideline also introduces a chapter dedicated to proper blood pressure measurement since all large randomized trials targeting blood pressure with pivotal outcomes used standardized preparation and measurement protocols adhered to by patients and clinicians. Based on previous and new evidence, in particular the Systolic Blood Pressure Intervention Trial (SPRINT) results, we propose a systolic blood pressure target of less than 120 mm Hg using standardized office reading for most people with chronic kidney disease (CKD) not receiving dialysis, the exception being children and kidney transplant recipients. The goal of this guideline is to provide clinicians and patients a useful resource with actionable recommendations supplemented with practice points. The burden of the recommendations on patients and resources, public policy implications, and limitations of the evidence are taken into consideration. Lastly, knowledge gaps and recommendations for future research are provided.